1977
DOI: 10.1084/jem.145.4.866
|View full text |Cite
|
Sign up to set email alerts
|

Mesenteric lymph node B lymphoblasts which home to the small intestine are precommitted to IgA synthesis.

Abstract: The fate of mesenteric lymph node lymphoblasts labeled with either [125I]iododeoxyuridine or [3H]thymidine can be studied after intravenous transfer into syngeneic mice both by measurement of radioactivity in various organs and by combined immunofluorescence and autoradiography of recipient tissues. Many of the lymphoblasts home to the lamina propria of the small intestine within hours of transfer; of these, many visibly secrete IgA. To determine whether the cells that will ultimately secrete IgA are already c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(38 citation statements)
references
References 20 publications
0
38
0
Order By: Relevance
“…The fact (table II) that some plaque-forming cells are de monstrable in the salivary gland does not imply that they must have been exposed to antigen there: many authors [e .g. Pierce and Gowans, 1975;McWilliams et al, 1977;Hall et al, 1972;Guy-Grand et al, 1974] have shown that the alimentary-tractassociated lymphoid tissues are a regu lar site for the 'homing' of circulating immunoblasts initially sensitised elsewhere. It seems likely that specific antibody-produc ing cells of the IgM as well as IgA class may move from the lower alimentary tract lymphoid tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The fact (table II) that some plaque-forming cells are de monstrable in the salivary gland does not imply that they must have been exposed to antigen there: many authors [e .g. Pierce and Gowans, 1975;McWilliams et al, 1977;Hall et al, 1972;Guy-Grand et al, 1974] have shown that the alimentary-tractassociated lymphoid tissues are a regu lar site for the 'homing' of circulating immunoblasts initially sensitised elsewhere. It seems likely that specific antibody-produc ing cells of the IgM as well as IgA class may move from the lower alimentary tract lymphoid tissues (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal conditions, IgA, the most abundant immunoglobulin isotype of the gut, provides protection against mucosal pathogens [66] by control of bacterial growth and prevention of adhesion to the intestinal epithelium [67,68]. As a reaction to the pathogen, IgA B cells start migrating from the PP to the mLN and then, following differentiation to IgA-secreting cells, home under the influence of chemokines to the intestinal lamina propria [69]. The theory of a link between PP or mLN and therefore LT and IgA production has been extensively investigated [70,71,72].…”
Section: Lt and Gastrointestinal Immune Homoeostasismentioning
confidence: 99%
“…The "homing" process of lymphoid cells is depending on coordinated lymphocyte migration and recirculation to the microenvironments that control their differentiation, survival, disperses the immunologic repertoire and targets effector lymphocytes to sites of antigenic insult. This "remarkable" tissue specificity has already been described and published in 70´s [29,[57][58][59]. The "virgin" lymphocytes show usually homogeneous recirculation through secondary lymphoid tissues but the memory and effector lymphocytes form distinct subgroups with tissue-selective/specific migratory capability to provide "appropriate" immune cells and locally effective immune reaction [10,[27][28][29][30][31].…”
Section: New Perspectivesmentioning
confidence: 90%